First records of the corinnid genera Allomedmassa Dankittipakul & Singtripop, 2014 and Medmassa Simon, 1887 from China, with the description of a new genus (Araneae: Corinnidae) - Jin, Chi; Zhang, Hongli; Zhang, Feng (Zootaxa, 2019)
Two corinnid genera, Allomedmassa Dankittipakul & Singtripop, 2014 and Medmassa Simon, 1887, are recorded from China for the first time, including five species, four of which are new to science: Allomedmassa mae Dankittipakul & Singtripop, 2014, A. bifurca sp. nov., A. crassa sp. nov., A. matertera sp. nov. and Medmassa torta sp. nov.. A new genus, Paramedmassa gen. nov., is erected with the type species P. day (Dankittipakul & Singtripop, 2014) comb. nov., which is transferred from Allomedmassa.